Bad kitty goes to the vet - Bruel, Nick (Bruel, Nick. Bad Kitty., 2016)
When Kitty gets sick, her family drags her to the vet. A shot induces a dream sequence in which Kitty must make amends for all the bad things she has done to Puppy if she hopes to get into PussyCat heaven one day.